Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Simplifying 5(2x + 1) = 3(x + -2) Reorder the terms: 5(1 + 2x) = 3(x + -2) (1 * 5 + 2x * 5) = 3(x + -2) (5 + 10x) = 3(x + -2) Reorder the terms: 5 + 10x = 3(-2 + x) 5 + 10x = (-2 * 3 + x * 3) 5 + 10x = (-6 + 3x) Solving 5 + 10x = -6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + 10x + -3x = -6 + 3x + -3x Combine terms: 10x + -3x = 7x 5 + 7x = -6 + 3x + -3x Combine terms: 3x + -3x = 0 5 + 7x = -6 + 0 5 + 7x = -6 Add '-5' to each side of the equation. 5 + -5 + 7x = -6 + -5 Combine terms: 5 + -5 = 0 0 + 7x = -6 + -5 7x = -6 + -5 Combine terms: -6 + -5 = -11 7x = -11 Divide each side by '7'. x = -1.571428571 Simplifying x = -1.571428571
x2 - 4 + (x - 2)2 = (x - 2)(x + 2) + (x - 2)2 = (x - 2)(x + 2 + x - 2) = 2x(x - 2)
Áp dụng BĐT AM - GM ta có :
\(\left(1+\frac{a}{b}\right)^5+\left(1+\frac{b}{a}\right)^5\ge2^5\left(\sqrt{\frac{a}{b}}\right)^5+2^5\left(\sqrt{\frac{b}{a}}\right)^5=32\left[\left(\sqrt{\frac{a}{b}}\right)^5+\left(\sqrt{\frac{b}{a}}\right)^5\right]\)
\(\ge32.2\sqrt{\left(\sqrt{\frac{a}{b}}\right)^5\left(\sqrt{\frac{b}{a}}\right)^5}=32.2=64\)(đpcm)
Dấu "=" xảy ra \(\Leftrightarrow a=b\)
g/ x(x-2)-x2=5x-7
\(\Leftrightarrow x^2-2x-x^2=5x-7\\ \Leftrightarrow7x=7\Leftrightarrow x=1\)
h/\(3x\left(x-7\right)+2\left(x-7\right)=0\\ \Leftrightarrow3x^2-19x-14=0\\ \)
\(\Leftrightarrow\left(x-7\right)\left(3x+2\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=7\\x=-\frac{2}{3}\end{matrix}\right.\)
\(1.A=14x^2+16x-21x-24=14x^2-5x-24\)
\(2.A=3x^3-2x^2-15x+14\)
\(3.A=x^4-x^3+2x^2+7x-5\)
\(4.A=x^4-7x^3+3x^2+21x-18\)
\(5.A=4x^2-y^2\)
\(6.A=x^3-8y^3\)
\(7.A=x^3+27y^3\)
\(8.A=x^2y^2-1\)